DECONSTRUCTING MAINSTREAM DISCOURSES OF CHILD AND YOUTH DEVELOPMENT AS IT CONNECTS TO SEXUALIZED VIOLENCE AGAINST CHILDREN - Lindner, Kylee; Kakuru, Doris (International Journal of Child, Youth and Family Studies, 2022)
This article reviews literature on survivors of child sexual abuse (CSA) who were preschool-aged when the abuse occurred, and applies critical discourse analysis to reveal power relations within this field of research. Utilizing themes of narrative theory, this article demonstrates how the current discourse has promoted a single story of developmental trajectories marred by entrenched deficits. The reviewed literature often utilized definitive language in describing a narrative of damage that not all survivors identify with. We critically examine this narrative as an expression of power that risks misrepresenting a large group of people. Additionally, we recommend that future research promote a discourse of multiple stories in which survivors have agency to author their own stories.